Nanostructure, optical, electronic, photoluminescence and magnetic properties of Co-doped ZrO2 sol–gel films - Baqiah, Hussein; Awang Kechik, Mohd Mustafa; Pasupuleti, Jagadeesh; Zhang, Na; Al-Hada, Naif Mohammed; Chien, Fat Chau; Qiang, Li; Shicai, Xu (Elsevier BV, 2023)
ZrO2 is a fascinating metal oxide with rich physical phenomenon and promised applications. In this study, the effects of chemical doping with Co+2 ions on nanostructure, electronic, optical, photoluminescence (PL), and magnetic properties of Zr1-xCoxO2 thin films (x = 0.0, 0.05, 0.1, and 0.15) prepared by sol–gel spin-coating method were investigated. The films exhibited a tetragonal structure with crystallinity improved with Co doping. Pure ZrO2 film showed a smooth surface morphology consisting of small particle size of 22 nm. The Codoped ZrO2 films exhibited well-ordered holes, and their size and number increased with Co doping up to x = 0.1 and then decreased at x = 0.15. Root-mean-square roughness increased from 1.1 nm for pure ZrO2 to 16.5 nm for film x = 0.15. The Co ions in the films existed in a 2 + valence state. Energy band gap decreased with Co doping and had values of 4.40, 4.396, 4.392, and 4.170 eV for the films with x = 0.0, 0.05, 0.1, and 0.15, respectively. The PL spectra of films x = 0.00 and 0.05 are mainly comprised of two emission peaks; intense peak centred at 370 nm and broad peak centred about 500 nm. As the Co concentration increased, two intense and sharp emission peaks emerged at 335 and 373 nm. The films showed soft hysteresis loop, and their magnetization was enhanced with the increase of Co content.